Effect of breast-feeding on pituitary-ovarian function after childbirth. Issue 5988 (11th October 1975) - Bonnar, J; Franklin, M; Nott, P N; Mcneilly, A S
Abstract : Pituitary and ovarian function at the end of pregnancy and during the first six weeks after delivery was investigated serially in women who fully breast-fed their infants and in women who did not. In the women who did not breast-feed the plasma prolactin level decreased rapidly and from the third day after delivery was significantly lower than in the breast-feeding mothers, reaching the normal range of the menstrual cycle by the third week of the puerperium. In the breast-feeding mothers the plasma prolactin was still raised six weeks after delivery. The levels of FSH in both groups were identical and increased over the third week of the puerperium. Plasma oestrogen fell steeply in both groups during the first two weeks after delivery. In the breast-feeding mothers plasma oestrogen remained depressed but increased in the non-lactating women, reflecting follicular development in the ovary in response to FSH; the plasma oestrogen levels were significantly higher in the non-lactating women from the 17th day of the puerperium onwards. These findings support the concept that in breast-feeding women prolactin delays the return of ovulation by inhibiting the ovarian response to FSH stimulation.